2018
DOI: 10.1016/j.ymgmr.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characteristics of colombian patients with mucopolysaccharidosis IVA, and description of a new galns gene mutation

Abstract: A study published in 2012 estimated incidence of MPS IVA, in 0.68 cases per 100, 000 live births in Colombia, and according to the Colombian Fund for High-Cost Diseases, in 2014 there were 15 people diagnosed with MPS IV. To enhance the knowledge of the disease in the country, we aimed to characterize clinical and molecular findings in 12 MPS IVA patients. Twelve patients were included in the study, with most patients of female gender (n = 7, 58,3%), age range 2 to 28 years, average weight 26 kg (17.6–43 kg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
3
0
4
Order By: Relevance
“…The GALNS enzyme activity in the KS positive patients ranged from undetectable to less than 10% of the total enzyme activity. Our results are consistent with that observed by Leong et al (12) in the Malaysian population and other reported studies (15,26,27).…”
Section: Discussionsupporting
confidence: 93%
“…The GALNS enzyme activity in the KS positive patients ranged from undetectable to less than 10% of the total enzyme activity. Our results are consistent with that observed by Leong et al (12) in the Malaysian population and other reported studies (15,26,27).…”
Section: Discussionsupporting
confidence: 93%
“…In a study conducted in 2018 in the Colombian population, the pathogenic p.Gly301Cys variant was reported in 51.6% of the alleles analyzed. [ 14 , 15 ] These results are consistent with a previous description in 1997, with a reported prevalence of 68.4% for the p.G301C mutation, considered as a founder mutation in the Colombian population [ 16 ]. At present, this mutation has also been reported in the Moroccan, Portuguese, French, Brazilian and Spanish populations, being more frequent in the latter (20%).…”
Section: Introductionsupporting
confidence: 91%
“…This wide allelic heterogeneity in GALNS mutations is what supports the broad spectrum of clinical phenotypes observed in patients with MPS IVA. A genotype-phenotype correlation has been reported in some groups of patients, [ 11 , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] making it even more important to insist on early diagnosis followed by prompt initiation of treatment, in order to improve prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this, in the present update, 89.2% of all c.1023C>G alleles were reported in Brazil. Variant c.901G>T [p.(Gly301Cys)] was the next most represented allele in Brazil (13.3% of all Brazilian alleles) and also accounted for 46.6% and 12.4% of alleles reported in Colombia and Canada, respectively (Moisan et al, 2020 ; Moreno Giraldo et al, 2018 ; Tapiero‐Rodriguez et al, 2018 ).…”
Section: Variantsmentioning
confidence: 99%